Germany and It Immigrants - Münz, Rainer (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
Germany has a total population of 82 million. 13 million residents of Germany –both citizens and non-citizens– were born outside today’s borders of Germany; 10 million of them immigrated after 1950. The article analyses the composition of the foreign-born population and of the legal foreign resident population. It also analyses the migration flows since the late 1930s for ethnic German and foreign immigrants, informs about naturalization and regional distribution of legal foreign residents and gives an account of the demographic impact of immigration to Germany.